1975
DOI: 10.1080/00207547508942984
|View full text |Cite
|
Sign up to set email alerts
|

Quality control practices

Abstract: This paper presents Borne case studies of quality control practices based on the authors' visits to Borne manufacturing industries. The statistical methods applied in each quality control programme are emphasized. IntroductionThe term quality control in its broad sense means the total activities of the staff of a company in carrying out its quality objectives. These objectives need not aim at producing the best quality that the manufacturer can possibly make, but the quality that can meet the consumer's satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Past research studies[e.g. 27,28] has concluded that the major barriers preventing the introduction of these techniques is lack of knowledge and little industry awareness. From the surveys carried out it was clear that many companies are introduced to online quality control by customers who specify its use.…”
Section: Proliferation Of Reliability Methods In the Manufacturing Industrymentioning
confidence: 99%
“…Past research studies[e.g. 27,28] has concluded that the major barriers preventing the introduction of these techniques is lack of knowledge and little industry awareness. From the surveys carried out it was clear that many companies are introduced to online quality control by customers who specify its use.…”
Section: Proliferation Of Reliability Methods In the Manufacturing Industrymentioning
confidence: 99%
“…Commenting on reports by Chiu & Wetherill (1975) and Saniga and Shirland (1977) that few practitioners implement economically designed procedures. Montgomery (199 I ) offers difficulty in estimating cost parameters as one possible reason.…”
Section: Approximate Values Forkmentioning
confidence: 95%